Pengaruh Populasi Sapi Perah, Tingkat Produksi, Dan Konsumsi Susu Sapi Terhadap Impor Susu Sapi Indonesia - Putu Oktaadi Putri (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the influence of dairy cattle population, production level, and milk consumption on the volume of imported milk in Indonesia. The background of the study is based on the condition of national milk demand which continues to increase along with population growth and changes in consumption patterns, while domestic production is still limited, resulting in a fairly high dependence on imports. The data used in this study is time series data for the period 1993–2022 with a total of 30 years of observations. The analytical method used is multiple linear regression with the help of SPSS 25 software. The results of the study indicate that simultaneously the variables of dairy cattle population, production level, and milk consumption significantly influence the volume of imported milk in Indonesia. The dairy cattle population variable has a negative and significant effect on imports. The domestic milk production level variable does not have a significant effect on imports. The cow's milk consumption variable has a positive and significant effect on imports.